Exporting SSIs in Haryana: Opportunities and Threats - Sharma, Reetu (Prabandhan: Indian Journal of Management, 2011)
The importance of SMEs in any economy cannot be overlooked as they form a major chunk in the economic activity of nations. India has nearly three million SMEs, which account for almost 50 per cent of industrial output. However, SMEs, which form the backbone of industrial development in India, are not export competitive and contribute to only about 34 percent of the exports. It is this feature of the SMEs that make it an ideal target to realize its potential export competitiveness. Drawing from the experiences of countries that have successfully promoted the export competitiveness of SMEs, this paper has identified ways in which SMEs in India can have an access to external markets through exports, which include simplification of procedures, incentives for higher production, preferential treatments to SMEs in the market development fund, linking up SMEs with Transnational Companies or large domestic exporting firms; and formation. This article focuses on a paradigm of eight keys for successful decision-making relative to export marketing by the small business firm. These keys for strategic decision making recommended for the small business firm desiring to be successful in export endeavours are: 1) Sell the know-how/products, 2) Goods must be properly serviced, 3) Deliveries must be on time, 4) Test marketing of the products,5) Research, 6) Initial attack, 7) Attitudes, 8) Communication. The article provides a decision-making paradigm that is useful to small business management personnel as well as export managers.